THE PSYCHOLOGY OF BETRAYAL IN “GONE GIRL” BY GILLIAN FLYNN - Safarova Zilola Tolibovna; Ergasheva Salomat Ravshan qizi (Bright Mind Publishing, 2025)
This article is aimed to explore the complex psychology of betrayal in the novel “Gone Girl” by Gillian Flynn, focusing on how dishonesty and manipulation shape the emotional and moral landscapes of the characters. The book’s portrayal of Amy and Nick Dunne shows how betrayal can be both a way to get back at someone and a sign of deeper psychological issues and social pressures. This study investigates the relationship between trust, identity, and control, revealing how Flynn illustrates the vulnerability of human relationships when love is intertwined with power and perception. Ultimately, “Gone Girl” transforms betrayal into both a psychological weapon and a means of self-preservation, challenging readers to question the boundaries between victim and villain, truth and illusion.
Keywords: Betrayal, psychology, manipulation, identity, trust, deception, marital conflict, power dynamics, self-preservation, Gillian Flynn, Gone Girl.